2018
DOI: 10.1186/s12873-018-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Provision of post-crash first aid by traffic police in Dar es Salaam, Tanzania: a cross-sectional survey

Abstract: BackgroundThe availability of prehospital trauma care is an important means of reducing serious injuries and fatalities associated with road traffic injuries (RTIs). Lay responders such as traffic police play an important role in the provision of prehospital trauma care to RTI victims, especially where there is no established prehospital care system. Therefore, the objective of the present study was to investigate knowledge, self-reported practice, and attitudes toward post-crash first aid among traffic police… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
(17 reference statements)
1
38
2
1
Order By: Relevance
“…We tested the hypothesis that a PFA educational program delivered to traffic police would lead to improved knowledge and increased confidence in first aid delivery skills. Before the training, police officers had low levels of knowledge and confidence in regard to administering first aid to RTI victims, a finding that is reflected in those of a previous survey in Tanzania (13). Post-training surveys immediately after training and after six months showed that there was a significant improvement in first aid knowledge and skills confidence among traffic police.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We tested the hypothesis that a PFA educational program delivered to traffic police would lead to improved knowledge and increased confidence in first aid delivery skills. Before the training, police officers had low levels of knowledge and confidence in regard to administering first aid to RTI victims, a finding that is reflected in those of a previous survey in Tanzania (13). Post-training surveys immediately after training and after six months showed that there was a significant improvement in first aid knowledge and skills confidence among traffic police.…”
Section: Discussionmentioning
confidence: 72%
“…A list of 340 police officers from a previous database regarding knowledge, self-reported practice, and attitudes of traffic police officers was used to proportionately select officers from jurisdictional areas of Kinondoni, Ilala and Temeke (13). A simple random sampling by drawing a YES/NO tickets from the box was used.…”
Section: Data Collection and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruitment process was left under the mandate of researchers who ensured rights of officers to participate or decline participation were maintained without interference from police management. A list of 340 police officers from a previous database regarding knowledge, self-reported practice, and attitudes of traffic police officers was used to proportionately select officers from jurisdictional areas of Kinondoni, Ilala and Temeke [13]. A simple random sampling by drawing a YES/NO tickets from the box was used.…”
Section: Data Collection and Proceduresmentioning
confidence: 99%
“…In Tanzania, traffic police officers are officially responsible for providing first aid and for facilitating the transport of injured people from the crash scene to the hospital, either independently or in collaboration with other lay responders. Although a first aid course is part of the curriculum during police officers' formal trainings, a previous study conducted to investigate their knowledge, practice, and attitudes toward care of RTI victims revealed that they have low levels of knowledge and poor practices [13]. Some of the reasons for this finding could be attributed to the fact that the curriculum and training approach to the management of road trauma victims is inadequate.…”
Section: Introductionmentioning
confidence: 99%